Catheter-Directed Thrombectomy: An Alternative in Massive Pulmonary Embolism - Andres Cordova Sanchez; Mostafa Vasigh; Oluwateniola Olatunde; Debanik Chaudhuri (Case Reports in Cardiology)
Massive pulmonary embolism (PE) is a life-threatening condition. The mainstay treatment is thrombolysis. Catheter-directed thrombectomy involves a group of new techniques that appear to have relatively low complications and mortality. These techniques have so far been studied mostly in submassive PE. We present a patient with massive PE that was successfully treated with catheter-directed thrombectomy.